The living of elderly people after stroke - Eglon Pauli; Marinês Tambara Leite; Larissa Bornholdt; Leila Mariza Hildebrandt; Sandra da Silva Kinalski; Margrid Beuter (Universidade Federal de Santa Maria, 2020)
Objective: to understand the living of elderly people after the occurrence of a Stroke (FAST). Method: qualitative and descriptive research. Data collected between January and March 2018 in three Family Health Strategies (FHS), through semi-structured interviews with elderly people, stroke victims, whose information was analyzed according to thematic analysis. Results: the data allowed the construction of three categories: the functional and social changes in the lives of elderly people after the occurrence of stroke; the (lack of) care after stroke in the understanding of the elderly person; and the future perspectives of the elderly person after stroke. Immediate and resolutive assistance in the hospital, the follow-up at FHS and the family involvement are essential for the rehabilitation of the elderly person. Final considerations: the results allowed us to understand the lives of the elderly patients, who showed changes in their daily lives after stroke, with different degrees of physical and psychological impairment.